2018
DOI: 10.21608/jappmu.2018.38949
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diets Contaning Green Bean (Phaseolus vulgaris) Vines Hay on Milk Yield, its Composition and Yoghurt Quality for Dairy Goats.

Abstract: ABESTRACTThis study was conducted to investigate the effect of inclusion green bean vines hay (GBVH) in replacing with clover hay (CH) in diets of Damascus goat does on nutrients digestibility, milk yield, milk composition, some blood parameters and yoghurt quality. Twenty-five lactating Damascus goat does with an average live body weight of 42.8±1.5kg at the 3 rd and 4 th parities were divided randomly into five similar groups (5 each) where each group received one of 5 experimental rations. The first group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 13 publications
(14 reference statements)
2
1
0
Order By: Relevance
“…Despite fat and protein contents had non-significant differences among treatments in fat content were markedly increased, while, protein content decreased in milk by increasing the replacement of CH with DBV in the tested ration. In agreement with the present findings, Abou El-Fadel et al (2018) revealed that milk yield a actual or 4% FCM was significantly increased with ration containing 75% green bean vines hay GBVH and 25% clover hay. Also milk yield increase insignificantly with T1 and T2 than T0, while T3 had produced the lowest amount of milk.…”
Section: Milk Yield and Compositionsupporting
confidence: 92%
See 2 more Smart Citations
“…Despite fat and protein contents had non-significant differences among treatments in fat content were markedly increased, while, protein content decreased in milk by increasing the replacement of CH with DBV in the tested ration. In agreement with the present findings, Abou El-Fadel et al (2018) revealed that milk yield a actual or 4% FCM was significantly increased with ration containing 75% green bean vines hay GBVH and 25% clover hay. Also milk yield increase insignificantly with T1 and T2 than T0, while T3 had produced the lowest amount of milk.…”
Section: Milk Yield and Compositionsupporting
confidence: 92%
“…In the present work SNF % were significantly decreased in T1 and insignificant decreased with T3 compared with that of control ration (T0). These results are in agreement with those reported by Abou El-Fadel et al (2018). Meanwhile, slightly improvement respecting milk TS was observed with the most tested rations compared with control diet with significant difference between the tested rations that having 50 and 100% DBV in replacing with CH in diets.…”
Section: Milk Yield and Compositionsupporting
confidence: 92%
See 1 more Smart Citation